Характеристика експортно-імпортної структури аграрної продукції України та нарощування її експортного потенціалу - Краснодєд, Тетяна Леонідівна; Краснодед, Татьяна Леонидовна; Krasnodied, Tetiana; Бакіна, Тетяна Володимирівна; Бакина, Татьяна Владимировна; Bakina, Tetiana (My University, 2016)
UK: В статті виявлено об’єктивну необхідність дослідження товарної структури експортованої та імпортованої сільськогосподарської і продовольчої продукції. Виявлено види вітчизняної продукції, що має найбільший попит на світовому ринку. Також визначено характер українського попиту на продукцію іноземних виробників. Водночас розглянуто резерви удосконалення експортно-імпортної структури аграрно-продовольчої продукції. Запропоновано напрями розробки раціональної стратегії нарощування експортного потенціалу України в контексті підвищення її конкурентоспроможності на світовому ринку продовольства. EN: In the international economy an important subject of study is the foreign trade and export-import operations. Meanwhile, in the agriculture sphere of Ukraine very relevant subject for study is export commodity structure analyze of agricultural and food products, as it is the necessary condition for developing of the Ukrainian export potential increase strategy in the agro-food products world market. The analysis of the export and import commodity structure of agricultural and food products showed that Ukraine is an active world agro-food market participant. It sells and buys raw materials and finished food products from foreign competitors. Many factors determine the volume and ratio of purchased and sold on the world market products. Milk and milk products, poultry eggs and natural honey predominated in export of live animals and animal products commodity structure. Cereal crops dominate in export vegetable products commodity structure considerable margin from other products in this category. Specific export share of adipose and oils and prepared food products in the total agricultural and food products exports is about the same level, in second place after grain. The imports of live animals and animal products commodity structure demonstrates relatively high level of fish and shellfish purchasing. The most imported animal origin products for this category is edible fruit nuts, coffee and tea. Prepared foods are the most imported categories in total agricultural and food products imports. Improving export structure and increasing the export volume of raw materials and agro-industrial products is the main way to increase of competitiveness in the global food market. Enhance competitiveness level of agricultural products and increase the export volume is necessary in several stages, starting with achieving stability in material and technical base, ending the formation of rational marketing concept. Ukrainian businesses have the opportunity to increase sales volumes in the agricultural and food products global market if there will be a mechanism to reduce production costs and sale export products costs. At the same time the using of innovative development of export potential for national agrarians is a prerequisite for increase and improving export and import commodity structure.
Agricultural products export and import characteristic of ukraine and increase its export potential
Keywords: зовнішня торгівля; світовий ринок; товарна структура; експорт; імпорт; сільськогосподарська продукція; продовольча продукція; конкурентоспроможність; foreign trade; world market; commodity structure; exports; imports; agricultural products; food products; the competitiveness